Improved DC-Link Voltage Controller for Photo Voltaic ON-Grid Systems - Husain A. Ismail; Ahmed Alenany; Belal Abozalam (IAES Indonesian Section, 2021)
The DC-link voltage is an essential intermediate stage between the DC/DC and DC/AC converters in solar energy system. Due to the voltage fluctuations and current disturbances, a controller should be suitably designed to maintain the DC-link voltage well stabilized. In this paper, a variant of an adaptive DC-link voltage controller is proposed, namely PI-Fuzzy controller. The proposed controller has a fixed integral gain, while the proportional gain is determined based on a set of Fuzzy logic inference rules. Moreover, an anti-windup mechanism is added to the proposed controller to overcome integrator windup when the actuator saturates. Simulation results show that the proposed controller provides better rejection of current disturbances and fastest rise-time comparing to recently proposed PI-controllers for the DC-link voltage control.